GOLD MORTGAGE FINANCING SYARIAH ON BANK SYARIAH MANDIRI - Henny Zurika Lubis, S.E., M.Si (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
The objective of this study was to determine how the implementationprocedures, assessment of gold pawn syariah and the contribution resulting fromthe gold pawn Bank Syariah Mandiri branch in Medan. The research method that Iuse in this paper is the descriptive method where researchers presented an analysisof the procedures for implementing the pledge of gold, gold pawn goods valuationmethod, advantages and disadvantages of the products and the contribution fromthe gold mortgage products on a standalone Islamic bank branch in Medan.It can be concluded procedures for implementing the pledge of gold syariaheasy enough, prospective customers fill out a form and carry a pledge in the form ofgold, assessment is in accordance with the standard price of gold is determined bydivision Islamic business, its advantages and disadvantages relevant enough, thecontribution resulting from product pawning gold syariah is a fee-based incomeincreased in value income, fee based income generated is an advantage comparedto other products.